2020
DOI: 10.1111/ane.13211
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decisions in women of childbearing age on valproate

Abstract: Introduction There are little data on the understanding and participation of women of childbearing age in decisions about their choice of antiepileptic drugs (AEDs). Valproate carries a risk of major congenital malformations, developmental and behavioural delay. For some, valproate is the only medication to prevent potentially life‐threatening seizures. Materials & Methods This was a cross‐sectional study of two groups of women of childbearing age; 50 taking valproate and 50 controls. Each patient completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Switching to lamotrigine can be limited by the required slow titration due to risk of Stevens-Johnson Syndrome [35], and switching to levetiracetam can be limited by mood side effects [36]. Outcome research can guide targeted preventive interventions and education programs, and specific recommendations can be made for each ASM [14,37]. There seems to be more need to educate certain groups such as GPs who prescribed the majority of ASMs.…”
Section: Discussionmentioning
confidence: 99%
“…Switching to lamotrigine can be limited by the required slow titration due to risk of Stevens-Johnson Syndrome [35], and switching to levetiracetam can be limited by mood side effects [36]. Outcome research can guide targeted preventive interventions and education programs, and specific recommendations can be made for each ASM [14,37]. There seems to be more need to educate certain groups such as GPs who prescribed the majority of ASMs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the 2020 survey results showed the level of compliance returning to the levels found in 2017 (compliance rate: 47%). In the UK, a survey conducted in 2017, 2 years after initial measures were introduced, revealed that 64% of women of childbearing potential treated with valproate reported that they had been informed and understood the risks associated with their treatment [21]. The analysis of the French National Health Insurance Database from 2011 to 2017 considering 114,936 female patients with epilepsy aged under 50 years found that prevalent use of valproate among girls and women of childbearing potential with epilepsy had decreased significantly after the implementation of RMMs, after the first referral in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium valproate use in pregnancy is not recommended and appropriate prescribing should be practised in this patient group. 22,26,27…”
Section: Discussionmentioning
confidence: 99%